Effects of a voter initiative on disparities in punishment severity for drug offenses across California counties. (June 2019) - Mooney, Alyssa C.; Neilands, Torsten B.; Giannella, Eric; Morris, Meghan D.; Tulsky, Jacqueline; Glymour, M. Maria
Abstract: Background: The jurisdiction where an offense is prosecuted significantly affects the severity of punishment for drug possession, creating geographic disparities in exposure to a social determinant of health. In California, felony conviction rates after drug possession arrests have historically varied enormously between counties. California Proposition 47 (Prop-47), passed in 2014, reduced drug possession offenses previously classified as felonies or wobblers (offenses for which prosecutors have discretion to file felony or misdemeanor charges) to misdemeanors. This study examines whether geographic variation in felony convictions after drug possession arrests was reduced, and whether effects were offset by changes in felony convictions for other offenses not addressed by Prop-47. Methods: Arrests made after the implementation of Prop-47 were propensity score matched to similar arrests prior to Prop-47 to account for compositional changes in arrests. This approach compares the outcomes of individuals likely to be arrested with or without the reclassification of drug offenses. We used mixed models to estimate the change in county variance in the probability of felony conviction. Results: The probability of a felony conviction among those arrested for Prop-47 drug offenses declined by 14 percentage points (95% CI: −0.16, −0.12), from 0.20 (95% CI: 0.18, 0.23) to 0.06 (95% CI: 0.06, 0.07). Counties with higher felony conviction probabilities pre-Prop-47 declined most, reducing cross-county variance. For those arrested for drug offenses unaffected by Prop-47, the probability of felony conviction declined by 7 percentage points (95% CI: −0.08, −0.05), from 0.34 (95% CI: 0.31, 0.37) to 0.27 (0.25, 0.29). Declines in both groups were driven by fewer felony convictions for Prop-47 drug offenses, with no increases in felony convictions for concurrent offenses. Conclusion: Reducing offense classifications for drug possession reduced previously large differences in the probability of felony convictions for people arrested for drug offenses in different counties. Highlights: Proposition 47 reduced prosecutorial discretion for drug possession in California. Felony conviction for drug offenses declined, with no increase for other offenses. Reduced large geographic inequalities in probability of felony conviction.